HSV-1 selectively packs the transcription factor Oct-1 into EVs to facilitate its infection - Ma, Yilei; Deng, Xiaomei; Zhou, Lingyue; Dong, Hongchang; Xu, Pei (Frontiers in Microbiology, 2023)
HSV-1 hijacks the cellular vesicular secretion system and promotes the secretion of extracellular vesicles (EVs) from infected cells. This is believed to facilitate the maturation, secretion, intracellular transportation and immune evasion of the virus. Intriguingly, previous studies have shown that noninfectious EVs from HSV-1-infected cells exert antiviral effects on HSV-1 and have identified host restrictive factors, such as STING, CD63, and Sp100 packed in these lipid bilayer-enclosed vesicles. Octamer-binding transcription factor-1 (Oct-1) is shown here to be a pro-viral cargo in non-virion-containing EVs during HSV-1 infection and serves to facilitate virus dissemination. Specifically, during HSV-1 infection, the nuclear localized transcription factor Oct-1 displayed punctate cytosolic staining that frequently colocalized with VP16 and was increasingly secreted into the extracellular space. HSV-1 grown in cells bereft of Oct-1 (Oct-1 KO) was significantly less efficient at transcribing viral genes during the next round of infection. In fact, HSV-1 promoted increased exportation of Oct-1 in non-virion-containing EVs, but not the other VP16-induced complex (VIC) component HCF-1, and EV-associated Oct-1 was promptly imported into the nucleus of recipient cells to facilitate the next round of HSV-1 infection. Interestingly, we also found that EVs from HSV-1-infected cells primed cells for infection by another RNA virus, vesicular stomatitis virus. In summary, this investigation reports one of the first pro-viral host proteins packed into EVs during HSV-1 infection and underlines the heterogenetic nature and complexity of these noninfectious double-lipid particles.